A systematic literature review on the influential family factors and cultural differences in parent-adolescent conflict among adolescents - Tanni, Khandaker Tasmina; Zainudin, Zaida Nor; Hassan, Siti Aishah; Mohamad Yusop, Yusni (Human Resource Management Academic Research Society, 2021)
Parent-Adolescent conflicts are associated with internalization and externalization problems, school maladjustment, and risky behavior of adolescents. Various studies have shown that the parent-child conflict is a risk factor for depression, anxiety, and low self-esteem among adolescents. The depression levels of adolescents living in families with high levels of conflict have been shown to be higher than those of adolescents who have a healthy relationship with the family. Hence, the purpose of this study was to identify the influential factors of parent-adolescent conflict in different cultures around the world and cultural differences within the context of parent-adolescent conflict. The methodology applied inclusion and exclusion criteria based on the Scopus database. A total of 18 articles were selected through the process. The findings of this review discuss the influential factors and cultural difference of parent-adolescent conflict in different countries and also explain the gaps and limitations in the literature assessing influential family factors of parent-adolescent conflict in different countries and different cultures around the world. The findings of this review are beneficial for psychotherapists and professional mental health support providers who work with families and adolescents where the therapists can design the needed plans of counseling for the clients by considering the importance of developing awareness among the parents and adolescents regarding their contribution to building a healthy relationship.